Clinical outcome comparison of percutaneous coronary intervention and bypass surgery in diabetic patients with coronary artery disease: a meta-analysis of randomized controlled trials and observational studies - Zhai, ChuanNan (Diabetol Metab Syndr, 2019)
BACKGROUND: The optimal revascularization technique in diabetic patients with complex coronary artery disease (CAD), including left main CAD and multivessel coronary disease (MVD), remains controversial. The current study aimed to compare adverse clinical endpoints of coronary artery bypass graft (CABG) and percutaneous coronary intervention (PCI) in patients with diabetes mellitus (DM). METHODS: Relevant studies were found from MEDLINE, OVID, Science Direct, Embase and the Cochrane Central database from January 2010 to April 2019. Risk ratio (RR) with 95% confidence interval (CI) was used to express the pooled effect on discontinuous variables. Outcomes evaluated were all-cause mortality, major adverse cardiac/cerebrovascular events (MACCE), cardiac death, myocardial infarction, stroke, and repeat revascularization. RESULTS: Sixteen studies were included (18,224 patients). PCI was associated with the increase risk for MACCE (RR 1.59, 95% CI 1.38–1.85), cardiac death (RR 1.76, 95% CI 1.11–2.80), MI (RR 1.98, 95% CI 1.53–2.57), repeat revascularization (RR 2.61, 95% CI 2.08–3.29). The risks for all-cause mortality (RR 1.23, 95% CI 1.00–1.52) and stroke (RR 0.71, 95% CI 0.48–1.03) were similar between two strategies. Stratified analysis based on studies design and duration of follow-up showed largely similar findings with the overall analyses, except for a significant increased risk of all-cause mortality (RR 1.32, 95% CI 1.04–1.67) in long-term group, and CABG was associated with a higher stroke rate compared to PCI, which are results that were found in RCTs (RR 0.47, 95% CI 0.28–0.79) and mid-term groups (RR 0.39, 95% CI 0.23–0.66). CONCLUSIONS: CABG was superior to PCI for diabetic patients with complex CAD (including left main CAD and/or MVD), but might be associated with a higher risk of stroke mid-term follow-up. Number of Protocol registration PROSPERO CRD 42019138505.